2022
DOI: 10.1002/mabi.202200281
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Responsive Glycopolymeric Nanoparticles for Enhanced Drug Delivery to Macrophages

Abstract: Macrophages play a diverse, key role in many pathologies, including inflammatory diseases, cardiovascular diseases, and cancer. However, many therapeutic strategies targeting macrophages suffer from systemic off-target toxicity resulting in notoriously narrow therapeutic windows. To address this shortcoming, the development of poly(propylene sulfide)-b-poly(methacrylamidoglucopyranose) [PPS-b-PMAG] diblock copolymer-based nanoparticles (PMAG NPs) capable of targeting macrophages and releasing drug in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…PMAG also enables the lyophilization and resuspension of glycoNPs, which could prevent the need for cold supply chains as long as the biologically active cargo remain bioactive through the lyophilization process. ,, Additionally, although we did not compare directly here, Reineke et al demonstrated improved stability of NPs coated in PMAG compared to PEG . PMAG also enables active targeting of macrophages, and as shown for the first time in these studies, dendritic cells. Thus, we believe that PMAG is an exciting surface engineering approach that is particularly well-suited to immunoengineering applications since it circumvents allergies to PEG, preserves NP architecture though lyophilization, and naturally targets NPs to APCs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…PMAG also enables the lyophilization and resuspension of glycoNPs, which could prevent the need for cold supply chains as long as the biologically active cargo remain bioactive through the lyophilization process. ,, Additionally, although we did not compare directly here, Reineke et al demonstrated improved stability of NPs coated in PMAG compared to PEG . PMAG also enables active targeting of macrophages, and as shown for the first time in these studies, dendritic cells. Thus, we believe that PMAG is an exciting surface engineering approach that is particularly well-suited to immunoengineering applications since it circumvents allergies to PEG, preserves NP architecture though lyophilization, and naturally targets NPs to APCs.…”
Section: Discussionmentioning
confidence: 87%
“…PDSMA facilitates the conjugation of protein antigens via disulfide bonds that can subsequently be reduced in the presence of elevated glutathione inside cells. MAG was chosen as an NP corona material because it provides outstanding colloidal stability, conserves NP structure through lyophilization (as shown here), and can improve APC uptake compared to PEGylation . We demonstrate the synthesis, physicochemical characterization, stimuli responsiveness, and bioactivity of the glycoNPs, which we show can promote robust activation of dendritic cells (DCs) in vitro .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[24][25][26] In addition, large numbers of macrophages are often recruited to the inflammatory sites, and elevated levels of ROS also increase the inflammatory factors secreted by macrophages, further exacerbating the inflammation. [27][28][29] ROS-responsive polymer vesicles are a good platform to release drugs at the site of thrombosis and/or inflammation with an excessive ROS concentration. [30][31][32] Phenylborate ester and thioether are typical groups with high ROS sensitivity and have been applied for the treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, large numbers of macrophages are often recruited at the inflammatory sites, and the increased ROS levels will also increase the inflammatory factors secreted by the macrophages, further exacerbating the inflammatory situation. [13,14] ROS-responsive polymers hold great promise in combating ROS-related diseases. [15] Various types of reactive groups have been explored in the construction of ROS-responsive materials such as thioether, selenium/tellurium, thioketal, aminoacrylate, boronic acid ester, polyoxalate ester and polyproline.…”
Section: Introductionmentioning
confidence: 99%